Efficacy and tolerability of preservative-free 0.0015% tafluprost in glaucoma patients: a prospective crossover study - Wonseok Lee; Sunghoon Lee; HyoungWon Bae; Chan Yun Kim; Gong Je Seong (BMC Ophthalmology, 2017)
Abstract Background The aim of this work is to evaluate efficacy and tolerability of preservative containing 0.0015% tafluprost and preservative-free 0.0015% tafluprost using a prospective crossover study. Methods Primary open angle glaucoma (POAG) and normotensive glaucoma (NTG) patients were randomized enrolled. Group 1 (“NPT to PT”) patients used preservative-free 0.0015% tafluprost (NPT) for 6 months and then changed to preservative containing 0.0015% tafluprost(PT) for 6 months. Group 2 (“PT to NPT”) patients used preservative containing 0.0015% tafluprost for 6 months and changed to preservative-free 0.0015% tafluprost for 6 months. At 1, 3, 6, 7, 9, and 12 months, we measured intraocular pressure for efficacy and graded corneal erosion, tear break-up time (TBUT), and subjective discomfort. Results A total of 20 patients and 20 eyes were enrolled. In Group 1 and 2, intraocular pressure was well controlled to approximately 14 mmHg (9.38–18.46% decrease). Generally, subjective satisfaction was improved after changing from PT to NPT (p = 0.03) and TBUT using PT was numerically inferior to that using NPT (p = 0.06) but not when changing from NPT to PT. Conclusion Both preservative containing and preservative-free 0.0015% tafluprost reduced intraocular pressure significantly. In addition, changing medication from PT to NPT might improve subjective satisfaction and tear break up time. Trial registration The trial registration number is NCT 03104621 (Apr/1/2017). Retrospectively registered.